Bisnis Media:Komersialisasi Kesehatan di Layar Televisi - Hariri, Muh Mirwan (Mekomda: Media Komunikasi Dakwah, 2024)
Media business is the principle of media to live independently derived from creativity that produces rupiah. Commercialization is the act of making something as merchandise. Commercialization of media has a dynamic and constant nature covering the operation of mass media to meet the needs of the market, one of which is in the field of health. Health commercialization is widely found in various media, one of which is television. Health discussions in the media no longer meet the needs of the public, because health in the media is only a business and commercial issue.